2010
DOI: 10.1164/rccm.201002-0172oc
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal Muscle Blood Flow Limitation during Exercise in Chronic Obstructive Pulmonary Disease

Abstract: During intense exercise in COPD, restriction of intercostal muscle perfusion but preservation of quadriceps muscle blood flow along with attainment of a plateau in cardiac output represents the inability of the circulatory system to satisfy the energy demands of locomotor and respiratory muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 34 publications
12
88
2
Order By: Relevance
“…In patients with COPD, chronically altered oxygen transport (351,352) and impaired oxygen use (176,(181)(182)(183)353) facilitate limb muscle oxidative stress (201,217,226,227,229,354) leading to nitroso-redox imbalance (355)(356)(357) and explaining post-transcriptional alterations (inhibition of S-nitrosylation) contributing to limb muscle dysfunction (201). Hypoxemia may also potentiate the inflammatory response (358), providing an additional mechanism linking hypoxia to specific cellular responses predisposing to muscle atrophy.…”
Section: Mechanisms Of Limb Muscle Dysfunction In Copdmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with COPD, chronically altered oxygen transport (351,352) and impaired oxygen use (176,(181)(182)(183)353) facilitate limb muscle oxidative stress (201,217,226,227,229,354) leading to nitroso-redox imbalance (355)(356)(357) and explaining post-transcriptional alterations (inhibition of S-nitrosylation) contributing to limb muscle dysfunction (201). Hypoxemia may also potentiate the inflammatory response (358), providing an additional mechanism linking hypoxia to specific cellular responses predisposing to muscle atrophy.…”
Section: Mechanisms Of Limb Muscle Dysfunction In Copdmentioning
confidence: 99%
“…Collectively, these studies (491)(492)(493) have shown that respiratory muscle unloading (via oxygen and/or heliox breathing, bronchodilation, and proportional-assist ventilation) improves leg muscle oxygen availability during exercise in patients with COPD. Recently, NIRS has been used in combination with the light-absorbing tracer indocyanine green dye to quantify regional blood flow in muscle and connective tissue during dynamic exercise in patients with COPD (352). Subsequent studies showed that respiratory muscle unloading improves locomotor muscle blood flow and oxygen delivery during exercise in patients with different patterns and degrees of dynamic hyperinflation (429,494).…”
Section: Assessment Of Muscle Oxygenation Using Near-infrared and Magmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to hyperinflation, the shortened diaphragm develops lower force (smaller pressure) during contraction, contributing to dyspnoea and reduced exercise tolerance [12]. It has been recently suggested that during intense exercise in COPD, reduction of respiratory (intercostals) muscle perfusion, but preservation of limb (quadriceps) muscle blood flow, along with attainment of a plateau in cardiac output, may represent the inability of the circulatory system to satisfy the energy demands of both locomotor and respiratory muscles [13]. In contrast, studies in these patients have shown diaphragmatic adaptations to greater oxidative capacity and resistance to fatigue [14].…”
Section: Pathophysiological Basis Question Does Airway Obstruction Ormentioning
confidence: 99%
“…There are also data on mechanisms underlying these effects. IMT enhances pulmonary oxygen uptake kinetics and high intensity exercise tolerance in humans, indicating that the enhanced exercise tolerance following IMT might be related, at least in part, to improved oxygen dynamics [18], thus potentially providing an answer for the suggested inability of the circulatory system to satisfy the energy demands of respiratory muscles [13]. Furthermore, the efficacy of IMT in inducing rib cage muscle remodelling is addressed unequivocally in the landmark study by RAMIREZ-SARMIENTO et al [19] who observed structural adaptations in external intercostal muscles following IMT in patients with COPD.…”
Section: Physiological Effects Questionmentioning
confidence: 99%